Pengaruh Profitabilitas, Leverage, dan Kepemilikan Institusional Terhadap Tax Avoidance - Sofiani, Yusarisna; Pratiwi, Ririh Dian (Faculty of Economics and Business Universitas Dian Nuswantoro, 2023)
Tax avoidance is a strategy to legally minimize the tax burden by taxpayers. This practice is mostly carried out by various types of companies, including companies in the mining sector. There are several factors that influence a company's practice of tax avoidance, including the level of profitability, leverage, and institutional ownership. The research was conducted in the 2015-2020 period. The independent variables as predictors in this study were profitability, leverage, and institutional ownership as independent variables and tax avoidance as the dependent variable. Samples were taken by considering various criteria and obtained the number of observations of 47 companies. The data used comes from the company's financial statements. The data were analyzed using multiple linear regression analysis with the help of SPSS version 25. The results of the study concluded that only the profitability variable had an effect on tax avoidance. Tax avoidance adalah sebuah strategi untuk meminimalkan beban pajak oleh wajib pajak seacara legal. Praktik ini banyak dilakukan oleh berbagai jenis perusahaan, termasuk perusahaan sector pertambangan. Terdapat beberapa faktor yang mempengaruhi suatu perusahaan dalam melakukan praktik tax avoidance, diantaranya adalah tingkat profitabilitas, leverage, dan kepemilikan institusional. Penelitian dilakukan pada periode 2015- 2020. Variabel bebas sebagai prediktor dalam penelitian ini profitabilitas, leverage, dan kepemilikan institusional sebagai variabel bebas dan tax avoidance sebagai variabel terikat. Sampel diambil dengan mempertimbangkan berbagai kriteria dan diperoleh jumlah observasi 47 perusahaan. Data yang digunakan bersumber dari laporan keuangan perusahaan.. Data dianalisis dengan analisis regresi linier berganda dengan bantuan SPSS versi 25. Hasil penelitian menyimpulkan bahwa hanya variable profitabilitas yang berpengaruh terhadap tax avoidance.Keywords:profitability, leverage, institutional ownership, tax avoidance